Role of statins in non-small cell lung cancer treatment: a systematic review and meta-analysis - Feng Li; Guangyu Liu (BMJ Open, 2025)
Objectives This systematic review and meta-analysis investigates the association between statin use and clinical outcomes in non-small cell lung cancer (NSCLC) patients, focusing on the therapeutic potential of statins and their impact on patient prognosis.Design The review includes a mix of prospective and retrospective cohort studies and randomised controlled trials to assess the relationship between statin use and NSCLC outcomes. ROBINS-I tool was used for assessing risk of bias, ensuring methodological rigour.Data sources A literature search was conducted across several databases, including MEDLINE (PubMed), EMBASE, Web of Science and the Cochrane Central Register of Controlled Trials. The databases were searched from inception to June 2024.Eligibility criteria Participants included adult NSCLC patients prescribed statins before or after diagnosis, with no restrictions on sex, age or disease stage. Interventions of interest were statin medications, typically used for hypercholesterolemia, and also investigated for anticancer properties. The primary outcome was overall survival (OS), with secondary outcomes including progression-free survival (PFS), cancer-specific survival and NSCLC recurrence.Data extraction and synthesis Data extraction was performed independently by two reviewers. Results were synthesised via a random-effects model, with forest plots illustrating HRs for OS and PFS.Results The meta-analysis included 25 studies with 51 536 NSCLC patients. Statin use was associated with improved OS (HR 0.77, 95% CI 0.70 to 0.85). A trend towards improved PFS was observed but did not reach statistical significance (HR 0.87, 95% CI 0.71 to 1.07).Conclusions Statin use may improve survival outcomes in NSCLC patients. These findings support the potential therapeutic role of statins in NSCLC management and call for further clinical trials.PROSPERO registration number CRD42016047524.